(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2010)
The article deal with some problems of Ukrainian arts and crafts, namely with artistic embroidery. It has been already proved that the studying of problem promotes the development of the creative skills of the studens.